THE EFFECT OF AUDIO VISUAL BASED PROBLEM BASED LEARNING ON CRITICAL THINKING ABILITY OF ELEMENTARY STUDENTS - Anita Rachman Ainur Rofiqoh; Meirza Nanda Faradita; Kunti Dian Ayu Afiani (Jurnal Cakrawala Pendas, 2023)
The purpose of this research is to: 1) determine the average pretest score students before using the audio-visual-based problem-based learning model, 2) knowing the average posttest of students after using the audio-visual-based problem-based learning model, 3) knowing the effect of audio-visual-based problem-based learning on the critical thinking skills of fifth grade elementary school students in subjects Science at MI Muhammadiyah 5 Surabaya. This study used a quantitative research approach and the type of research used was Pre-Experimental research . The design used by the researcher is the One Group Pretest-Posttest Design with one class as the research subject. The data analysis technique in this study was the normality test and the one sample test using the one sample test method with the help of SPSS. The results of the study: 1) the average critical thinking ability of students before using the audio-visual-based problem-based learning model is 57.50. 2) the average critical thinking ability of students after using the audio-visual-based problem-based learning model is 88.43. 3) the results of the one sample T-test data analysis using the one sample T technique show a significance value of <0.05, which is 0.000. The conclusion of this research is that learning using problem-based learning based on audio-visual models can improve elementary students' critical thinking skills. Tujuan dari penelitian ini adalah untuk: 1) mengetahui rata-rata nilai pretest siswa sebelum menggunakan model pembelajaran berbasis masalah berbasis audio visual, 2) mengetahui rata-rata nilai posttest siswa setelah menggunakan model pembelajaran berbasis masalah berbasis audio visual, 3) mengetahui pengaruh pembelajaran berbasis masalah berbasis audio visual terhadap kemampuan berpikir kritis siswa kelas V SD pada mata pelajaran IPA di MI Muhammadiyah 5 Surabaya. Penelitian ini menggunakan pendekatan penelitian kuantitatif dan jenis penelitian yang digunakan adalah penelitian Pre-Experimental. Desain yang digunakan oleh peneliti adalah One Group Pretest-Posttest Design dengan satu kelas sebagai subjek penelitian. Teknik analisis data pada penelitian ini adalah uji normalitas dan uji beda menggunakan metode one sample t-test dengan bantuan SPSS. Hasil penelitian: 1) rata-rata kemampuan berpikir kritis siswa sebelum menggunakan model pembelajaran berbasis masalah berbasis audio visual adalah 57,50. 2) rata-rata kemampuan berpikir kritis siswa setelah menggunakan model pembelajaran berbasis masalah berbasis audio visual adalah 88,43. 3) hasil analisis data uji-t satu sampel dengan menggunakan teknik one sample T-test menunjukkan nilai signifikansi < 0,05 yaitu 0,000. Kesimpulan dari penelitian ini adalah pembelajaran dengan menggunakan model pembelajaran berbasis masalah berbasis audio visual dapat meningkatkan kemampuan berpikir kritis siswa SD.